Antenatal Hypoxia and Programming of Glucocorticoid Receptor Expression in the Adult Rat Heart - Lv, Juanxiu; Ma, Qingyi; Dasgupta, Chiranjib; Xu, Zhice; Zhang, Lubo (Frontiers in Physiology, 2019)
Glucocorticoid receptor (GR) signaling is critical for development and function of the heart. Our previous study demonstrated that gestational hypoxia induced epigenetic repression of the GR gene in the developing heart. The present study aims to determine that the alterations of promoter methylation level and epigenetic repression of the GR gene in the developing heart in response to maternal hypoxia is sustained in adult offspring and potential gender differences in the programming of GR gene. Pregnant rats were treated with 10.5% O2 from gestational day 15 (E15) to 21 (E21). Hearts were isolated from 5 month-old male and female offspring with the developing stage being equivalent to 18 year-old human. GR mRNA and protein abundance was determined with real time qRT-PCR and Western blot. GR gene promoter methylation and binding of transcription factors were measured with methylated DNA immunoprecipitation (MeDIP) and Chromatin immunoprecipitation (ChIP). The results showed that antenatal hypoxia significantly decreased the expression of GR mRNA and protein in the hearts of adult male offspring, but not in females, which is ascribed to the differential changes of alternative exon1 mRNA variants of GR gene in male and female hearts in response to prenatal hypoxia. In addition, the downregulation of GR expression in the male heart was correlated with increased methylation levels of CpG dinucleotides in promoters of exon 14, 15, 16, 17, and 110, which resulted in a decrease in the binding of their transcription factors. Thus, the study reveals that antenatal hypoxia results in a reprogramming and long-term change in GR gene expression in the heart by hypermethylation of GR promoter in a sex-differential pattern, which provides a novel mechanism regarding the increased vulnerability of heart later in life with exposure of prenatal hypoxia.